2008
DOI: 10.1113/expphysiol.2007.040972
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants attenuate oxidative damage in rat skeletal muscle during mild ischaemia

Abstract: We have previously shown oxidative stress and oedema, caused by both xanthine oxidasederived oxidants and infiltrating neutrophils, within skeletal muscle after contractile-induced claudication. The purpose of this study was to determine whether supplementation with antioxidant vitamins attenuates the oxidative stress, neutrophil infiltration and oedema associated with an acute bout of contractile-induced claudication. Rats received vehicle, vitamin C, vitamin E or vitamin C + E for 5 days prior to contractile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…The antioxidant defense system can be augmented with appropriate dietary levels of antioxidants and/or supplementation. A number of studies have been conducted in an attempt to improve antioxidant systems via exogenous administration of antioxidant supplementation [119][120][121][122][123]. Rebrin et al [124] investigated the effects of supplementation with a combination of antioxidants on oxidative stress in skeletal muscle tissue homogenates and mitochondria in senescence-accelerated mice.…”
Section: Effects Of Antioxidant Supplementation On Antioxidant Systemmentioning
confidence: 98%
“…The antioxidant defense system can be augmented with appropriate dietary levels of antioxidants and/or supplementation. A number of studies have been conducted in an attempt to improve antioxidant systems via exogenous administration of antioxidant supplementation [119][120][121][122][123]. Rebrin et al [124] investigated the effects of supplementation with a combination of antioxidants on oxidative stress in skeletal muscle tissue homogenates and mitochondria in senescence-accelerated mice.…”
Section: Effects Of Antioxidant Supplementation On Antioxidant Systemmentioning
confidence: 98%
“…In this context, for preventing harmful effects of oxidative stress, many antioxidant agents, such as vitamin E, melatonin, retinol, β-carotene, omega-3, resveratrol, allopurinol, melatonin, Nacetylcysteine, zinc aspartate, and caffeic acid phenethyl ester, vitamin C, coenzyme Q10, and acetylcysteine have been used with different success rates. [46][47][48][49][50] Although numerous experimental animal studies have confirmed the efficacy of antioxidants in reducing short-term damaging effects of testicular torsion, different antioxidant agents have been investigated to reduce the short-and long-term reperfusion damage on the testes. Anti-apoptotic, anti-inflammatory, and antioxidant properties of oxytocin have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, the model used here has previously been used by our group, and others, to mimic exercise claudication (17,24,25,27). We have previously shown, using this model, that force production from the triceps surae muscle group decreases by ϳ10% in control limbs and ϳ50% in ligated limbs after 15 min of stimulation (24), and by ϳ15% and 70% in control and ligated limbs, respectively, after 30 mins of stimulation (24,25,27). The small decrease in control limbs demonstrates that the stimulation protocol is not intense.…”
Section: Contractile Claudication Modelmentioning
confidence: 99%
“…Two days following the ligation or sham surgery, in vivo muscle contractions began using a stimulation protocol previously optimized to cause a significant decrease in force production from limbs in which the femoral artery is ligated, but not in control limbs (24,25,27). The decrease in force production indicates insufficient oxygen delivery to the muscles.…”
Section: Contractile Claudication Modelmentioning
confidence: 99%